2016
DOI: 10.1145/2842604
|View full text |Cite
|
Sign up to set email alerts
|

Geoparsing and Geosemantics for Social Media

Abstract: In recent years there has been a growing trend to use publically available social media sources within the field of journalism. Breaking news has tight reporting deadlines, measured in minutes not days, but content must still be checked and rumours verified. As such journalists are looking at automated content analysis to pre-filter large volumes of social media content prior to manual verification. This paper describes a real-time social media analytics framework for journalists. We extend our previously publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…And some research on the credibility of users [61,62] and some others try to determine coordinated users who behave together and manipulate data content [63]. And studies claim social media is full of rumors and most part of the accountholders spreading wrong information while there are emergencies and do not correct the content even if they are informed later [64,65]. In respect to this, social media data requires to be assessed without removing any data but accepting all these deficits and considering them with the nature of itself, since it is not possible to control each user credibility in real-time without historical data or demographic information.…”
Section: Discussionmentioning
confidence: 99%
“…And some research on the credibility of users [61,62] and some others try to determine coordinated users who behave together and manipulate data content [63]. And studies claim social media is full of rumors and most part of the accountholders spreading wrong information while there are emergencies and do not correct the content even if they are informed later [64,65]. In respect to this, social media data requires to be assessed without removing any data but accepting all these deficits and considering them with the nature of itself, since it is not possible to control each user credibility in real-time without historical data or demographic information.…”
Section: Discussionmentioning
confidence: 99%
“…Twitter) and analyze the best algorithms for jointly estimating the real location of Twitter events. The scalable architecture used for geoparsing and geosemantics extraction in the EU REVEAL project [13] included features like the tweet content, position of the terms, part-of-speech (POS) sets, and 3-gram feature sets that combined named entities with their POS tags. It is clear that the key to obtaining good results is to focus on continuously improving the NEL pipelines.…”
Section: Named Entity Linking Systemsmentioning
confidence: 99%
“…Through two-way transmission, the users become both the receivers and the creators of new media content. Some studies have suggested that users are attached to their personal preferences, opinions, and relative personal influence when they create new media content [7][8]. This has ensured that new media content in the transmission process allows users can form a certain ship network and become an essential part of the new media time.…”
Section: Introductionmentioning
confidence: 99%